KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM (Studi Deskriptif Kualitatif di SMP Negeri 8 Lubuklinggau) - Fitriyani Fitriyani (El-Ghiroh : Jurnal Studi Keislaman, 2017)
The purpose of this research is to describe about thr principal managerial skill in improving the professionalism of the teacher of Islamic Religius Education. The method of this research was descriptive qualitative. The main subject of this research are principal, teachers of Islamic religius education, teacher, staffs, and student. The data colleted in this research analyzed with observation technique, interview, and documemntation techneique. The general result of this research showed that the principal manajerial skills in improving the professionalism of Islamic religious education teachers at Public Junior High School Number 8 Lubuklinggau already performing well, although not optimal.